2019
DOI: 10.1038/s41433-019-0521-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Rotational stability and its related factors of a single-piece acrylic toric intraocular lens

Abstract: Purpose In the present study, we aimed to evaluate the early postoperative rotational stability of TECNIS toric intraocular lens (IOL) and analyse its correlation with preoperative and intraoperative parameters. Methods A total of 102 eyes from 87 cataract patients who underwent implantation of TECNIS toric IOL during July 2016 to November 2017 were enrolled in this retrospective study. Preoperative parameters including corneal astigmatism, axial length (AL), lens thickness (LT), anterior chamber depth (ACD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
1
29
1
Order By: Relevance
“…Studies found a maximum rotation from 1.8 to 95 810-17 in the Acrysof and 8 to 45.32 8 in the Tecnis IOL. 16,[18][19][20][21][22] In our study, 1 Acrysof IOL rotated 17.6 8 after 1 hour and 27.2 8 from 1 hour to 1 week in the same direction. In total, this IOL showed 44.8 degrees of rotation during the first week.…”
Section: Resultssupporting
confidence: 48%
“…Studies found a maximum rotation from 1.8 to 95 810-17 in the Acrysof and 8 to 45.32 8 in the Tecnis IOL. 16,[18][19][20][21][22] In our study, 1 Acrysof IOL rotated 17.6 8 after 1 hour and 27.2 8 from 1 hour to 1 week in the same direction. In total, this IOL showed 44.8 degrees of rotation during the first week.…”
Section: Resultssupporting
confidence: 48%
“…However, some scholars did not find the correlation between the IOL rotation and AL in myopic eyes [8]. Our previous research has discovered the correlation between toric IOL rotation and LT, AL and area of capsulorhexis in eyes of various axial lengths and a positive correlation between AL and toric IOL rotation [9]. The controversy about the possible correlation between the AL and IOL rotation remains furious.…”
Section: Introductionmentioning
confidence: 94%
“…It may act as a sliding film between IOL rear surface and posterior capsule), especially for IOLs with large diameter and/or plate-haptic design. 21 Furthermore, it has been discussed in the past in various studies whether remaining OVD behind the IOL could act as channels for lens epithelial cell growth (LEC) and thus for faster posterior capsule opacification (PCO) development. 22 In addition, further advantages, such as an intraoperative increase in contrast (when using a suitable microscopy light source) and improved control of the amount of OVD injected, could be observed when using Pe-Ha-Blue®PLUS.…”
Section: Discussionmentioning
confidence: 99%